Chemical Organics Removal Through Combination of Constructed Wetland and Electrolytic System - Wang, Hao; Li, Xuejin; Cao, Guoping; Zhang, Lei (Asian Journal of Chemistry, 2012)
In this study, secondary effluent of wastewater treatment plants in Tangshan area was used. Horizontal zeolite wetland was carried out treating it. Zeolite wetlands showed different behaviours for nitrogen removals. Under the optimum hydraulic loading rate, the primary pollutions were removed to a large extent. Meanwhile, electrochemical oxidation was adopted to advancedly treated secondary effluent of wastewater treatment plants. The removal effect of major pollutants of constructed wetland effluent was mainly investigated and the main chemical reaction path of the removal of organic matter by electrochemical method was discussed preliminarily. The results showed the best removal ratio of organics matter was 58.2 % after dosing NaCl on the condition of different electrolysis time and constant current 5A ( namely the current density 7.4 mA/cm2).